N-Type field effect transistors based on rigid rod and liquid crystalline alternating copoly(benzobisoxazole) imides containing perylene and/or naphthalene - Kolhe, Nagesh B.; Asha, S. K.; Senanayak, Satyaprasad P.; Narayan, K. S. (Journal of Physical Chemistry B, 2010)
The synthesis, characterization, and device studies of poly(benzobisoxazole imide)s containing perylene or naphthalene units in an alternating fashion with the oxazole unit are described. Photoinduced energy transfer and charge separation were studied in methanesulfonic acid (MSA) solution via absorption, excitation, and steady-state fluorescence studies. Excitation of the bisoxazole moiety resulted in enhanced emission from the perylene bisimide unit as a result of FRET (Forster resonance energy transfer). The influence of the imide substitution into the linear chain of poly(benzobisoxazole) (PBO) on its solid-state packing was examined by wide-angle X-ray diffraction (WXRD) analysis. Bottom contact field effect transistors (FET) based on thermally annealed polymer films were fabricated and studied. The polymers showed n-type charge transport and current modulation with an on/off ratio greater than 10(2). It was observed that the FETs consisting of the random copolymer of bisoxazole containing both perylene as well as naphthalene bisimide units had higher performance parameters such as better mobility (mu e) and I(on)/I(off) ratio compared to those of the pristine systems.

Structure engineering of naphthalene diimides for improved charge carrier mobility: self-assembly by hydrogen bonding, good or bad? - Kolhe, Nagesh B.; Devi, R. Nandini; Senanayak, Satyaprasad P.; Jancy, B.; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry, 2012)
Two families of naphthalene diimide (NDI) derivatives were compared and contrasted for the effect of self-assembly on charge carrier transport. One series of NDI derivatives had a terminal phenyl ring attached to a hexyl spacer substituted naphthalene core either through an ester or an amide linkage (NDI-E and NDI-A, respectively), while the other series had a 3,4,5-tridodecyloxy phenyl unit (NDI-E3, NDI-A3) instead of the terminal phenyl unit. Solution processed thin films of these molecules exhibited n-type charge transport characteristics in a bottom gate top contact organic field effect transistor (OFET) geometry. The amide derivatives showed evidence of self-organization with observation of red shifted aggregate emission in solution as well as solid state. Variable temperature FTIR studies in the solid state confirmed the existence of strong hydrogen bonding which could be broken only at very high temperature. However, contrary to expectations, the NDI ester derivatives showed better device efficiency with electron mobilities in the range 8.5 x 10(-3) to 2 x 10(-2) cm(2) V-1 s(-1) and on/off ratio similar to 10(4). The thin film crystallinity and morphology of NDI-E and NDI-A were examined through X-ray diffraction and atomic force microscopy (AFM). The correlation of crystallinity, hydrogen bonding and charge carrier mobility was studied using energy minimized structures from density functional theory (DFT). The higher electron mobility of ester linked NDI derivatives over the amide linked ones was attributed to the freedom in charge transport pathways offered by a three dimensional crystalline organization in the ester compared to the restricted directional hydrogen bonding interaction in the amide derivatives.

Nanostructured crystalline comb polymer of perylenebisimide by directed self-assembly: poly(4-vinylpyridine)-pentadecylphenol perylenebisimide - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Advanced Functional Materials, 2013)
Well defined nanostructured polymeric supramolecular assemblies are formed when an asymmetric perylenebisimide substituted with ethylhexyl chains on one end and functionalized with 3-pentadecylphenol at the other termini (PDP-UPBI) is complexed with poly(4-vinylpyridine) (P4VP) via a non-covalent specific interaction such as hydrogen-bonding. The resulting P4VP(PDP-UPBI)(n) complexes are fully solution processable. The bulk structure and morphologies of the supramolecular film studied using small angle and wide angle X-ray scattering reveals highly crystalline nature of the complex. Thin film morphology of the 1:1 complex analyzed using transmission electron microscopy shows uniform lamellar structures in the domain range of 5-10 nm. A clear trend of improved electrical parameters in P4VP(PDP-UPBI) system compared to pristine (PDP-UPBI) is observed from space charge limited current measurements. In short, a simple and facile method to obtain spatially defined organization of n-type semiconductor perylenebisimide molecules using hydrogen bonding interactions with P4VP as the structural motif is showcased herein.

Nanostructured donor-acceptor self assembly with improved photoconductivity - Saibal, B.; Ashar, A. Z.; Devi, R. Nandini; Narayan, K. S.; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Nanostructured supramolecular donor-acceptor assemblies were formed when an unsymmetrical N-substituted pyridine functionalized perylenebisimide (UPBI-Py) was complexed with oligo(p-phenylenevinylene) (OPVM-OH) complementarily functionalized with hydroxyl unit and polymerizable methacrylamide unit at the two termini. The resulting supramolecular complex [UPBI-Py (OPVM-OH)](1.0) upon polymerization by irradiation in the presence of photoinitiator formed well-defined supramolecular polymeric nanostructures. Self-assembly studies using fluorescence emission from thin film samples showed that subtle structural changes occurred on the OPV donor moiety following polymerization. The 1:1 supramolecular complex showed red-shifted aggregate emission from both OPV (similar to 500 nm) and PBI (similar to 640 nm) units, whereas the OPV aggregate emission was replaced by intense monomeric emission (similar to 430 nrn) upon polymerizing the methacrylamide units on the OPVM-OH. The bulk structure was studied using wide-angle X-ray diffraction (WXRD). Complex formation resulted in distinct changes in the cell parameters of OPVM-OH. In contrast, a physical mixture of 1 mol each of OPVM-OH and UPBI-Py prepared by mixing the powdered solid samples together showed only a combination of reflections from both parent molecules. Thin film morphology of the 1:1 molecular complex as well as the supramolecular polymer complex showed uniform lamellar structures in the domain range <10 rim. The donor-acceptor supramolecular complex [UPBI-Py (OPVM-OH)](1.0) exhibited space charge limited current (SCLC) with a bulk mobility estimate of an order of magnitude higher accompanied by a higher photoconductivity yield compared to the pristine UPBI-Py. This is a very versatile method to obtain spatially defined organization of n and p-type semiconductor materials based on suitably functionalized donor and acceptor molecules resulting in improved photocurrent response using self-assembly.
Keywords: donor-acceptor; hydrogen bonding; oligo(p-phenylenevinylene); Perylenebisimide; photoconductivity; supramolecular polymeric nanostructures

Naphthalene diimide copolymers with oligo(p-phenylenevinylene) and benzobisoxazole for balanced ambipolar charge transport - Kolhe, Nagesh B.; Ashar, A. Z.; Narayan, K. S.; Asha, S. K. (Macromolecules, 2014)
A series of alternating and random donor (D)–acceptor (A) copolymers based on naphthalene diimide (NDI) as the acceptor and oligo(p-phenylenevinylene) (OPV) or benzobisoxazole (BBO) as the strong and weak donor, respectively, were designed and synthesized by Suzuki coupling and Horner–Wadsworth–Emmons polymerization. The effect of the varying donor strength of OPV and BBO on the photophysical, electrochemical, and semiconducting properties of the polymers was investigated. Absorption and emission spectra recorded for dilute chloroform solution and thin film showed increased intramolecular charge transfer for NDI-alt-OPV polymer compared to NDI-alt-BBO polymer. Cyclic voltammetry studies along with DFT (density functional theory) studies at the B3LYP/6-31g* level gave insight into the energy level (HOMO/LUMO) and molecular orientation of donor and acceptor along the polymer backbone. NDI-alt-OPV polymer exhibited rigid coplanar structure with extended π-conjugation which induced backbone planarity and crystallinity to the polymer. The inherent poor solubility of the NDI-alt-BBO prevented further device characterization of this polymer. Random copolymer having maximum 30% incorporation of BBO comonomer in NDI-r-OPV/BBO was found to be soluble for further characterization. Compared to NDI-alt-OPV, lowering of both energy levels LUMO (∼0.2 eV) and HOMO (∼0.5 eV) was observed for both NDI-alt-BBO and the NDI-r-OPV/BBO. Bottom gate–top contact organic field effect transistors (OFETs) of NDI-alt-OPV exhibited balanced ambipolar charge transport with average electron and hole mobility of 3.09 × 10–3 cm2 V–1 s–1 and 2.1 × 10–3 cm2 V–1 s–1, respectively, whereas the random copolymer incorporating both OPV and BBO units NDI-r-OPV/BBO showed dominant n-type charge transport with moderate 4 × 10–4 cm2 V–1 s–1 average electron mobility. The present work thus highlights the structure–property relationship and the electronic tunability required in this class of NDI-based polymers to produce ambipolar transistors.

Supramolecular P4VP-pentadecylphenol naphthatenebisimide comb-polymer: mesoscopic organization and charge transport properties - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A supramolecular comb polymer of pentadecyl phenol (PDP) substituted naphthalenebisimide (PDP-UNBI) with poly(4-vinylpyridine) (P4VP) is reported. The mesoscopic organization within the P4VP(PDP-UNBI), complexes was studied using wide-angle X-ray diffraction (WXRD) technicjues. The packing diagram obtained from the single-crystal XRD analysis of the PDP-UNBI crystals gave a clear picture of the initial arrangement present in self-associated PDP-UNBI alone. Correlating this with the XRD data of the hydrogen-bonded polymer complex provided insight into the probable packing of the P4VP chains within the crystalline lattice of PDP-UNBI leading to a highly ordered lamellar packing. Transmission electron microscopy (TEM) revealed the uniform mesomorphic lamellar structures in the domain range of similar to 5-10 nm. Furthermore, the charge carrier mobility measurements observed from space-charge-limited current (SCLC) measurements demonstrated that transport behaviour of the hydrogen-bonded P4VP(PDP-UNBI) complex (2 x 10(-2) cm(2) V-1 s(-1)) was comparable to that of the crystalline naphthalenebisimide molecule itself (9 x 10(-3) cm(2) V-1 s(-1)), which is a great achievement, since the complex now offers a package of solution-processable n-type semiconductor polymer with mobility equivalent to that of a small crystalline molecule.